Study of the spectrum and antibiotic sensitivity of the respiratory tract microbiota of newborns with infectious complications during long-term mechanical lung ventilation - Levchenko , Bohdan (The Ukrainian Scientific Medical Youth Journal, 2024)
determining the structure of leading microbial colonizers of the respiratory tract as potential causative agents of ventilator-associated pneumonia and their sensitivity to antibacterial drugs plays an important role in choosing effective tactics for etiotropic therapy of newborns. According to the data of scientific publications, the etiological structure of infectious complications associated with long-term respiratory support in newborns is known to have certain features. The spectrum of nosocomial microbial pathogens and their sensitivity to antimicrobial drugs are among them. The patients of early age are characterized by a number of peculiarities of anatomical and physiological characteristics and the qualitative and quantitative composition of the microbiota of the respiratory tract. In order to form ideas about the determining causative agents of VAP in newborns, it was advisable to conduct a microbiological study of the species composition of microorganisms associated with this infectious complication, as well as to determine their sensitivity to antibiotics recommended by the management protocols of the corresponding pathology. To study and solve this problem, it is necessary to study the spectrum and antibiotic sensitivity of the causative agents of VAP. A prospective study was conducted in 69 newborns with VAP (2020 - 2023), who were treated in the Neonatal Intensive Care Unit (NICU) of the Vinnytsia Regional Children’s Clinical Hospital (VRCCH) and consisted in studying the composition of the microbiota and antibiotic sensitivity. We took into account opportunistic microorganisms that are not characteristic of this biotope of the respiratory tract of newborns who were diagnosed with VAP during long-term mechanical ventilation. As a result of the prospective analysis of the microbiological study of the microbiota of 69 newborns, 82 microorganisms - etiologically significant pathogens of VAP - were isolated and identified. Thus, according to the data of our bacteriological studies, 17 Gram-positive and 65 Gram-negative pathogens of VAP were isolated and identified in NICU VRCCH for 2020-2023. As a result of the study of antibiotic sensitivity of VAP pathogens in newborns, the following trends were observed. Low sensitivity of Acinetobacter baumannii to ceftazidime, aztreonam, imipinem, meropenem, amoxicillin, piperacillin, levofloxacin, ciprofloxacin was established. And sensitive to amikacin, gentamicin and cefoperazone-sulbactam. High rates of resistance of Pseudomonas aeruginosa to ceftazidime, doxycycline, imipinem, meropenem, gentamicin, piperacillin, levofloxacin, ciprofloxacin, ofloxacin were established. The best indicators of sensitivity of P. aeruginosa to amikacin, cefoperazone-sulbactam and tobramycin were found. According to the results of the sensitivity of K. pneumoniae to antibiotics, resistance to all antibiotics was established. The development of resistance of Staphylococcus aureus to azithromycin, norfloxacin, cefotaxime, benzylpenicillin has been established. The indicators of S. aureus sensitivity to amikacin, tetracycline and vancomycin turned out to be the best. We took into account opportunistic microorganisms that are not typical for this biotype of the airways of newborns who were diagnosed with VAP during long-term mechanical ventilation. The results of the study indicate the need to take into account the data of a microbiological study with the mandatory identification of isolated pathogens, their microbial load at the site of infection, determining their antibiotic sensitivity is of crucial importance in the selection of etiotropic treatment tactics for newborns with VAP.